24‐hour activity for children with cerebral palsy: a clinical practice guide - Verschuren, Olaf (Dev Med Child Neurol, 2020)
The association between physical activity and health has been clearly established, and the promotion of physical activity should be viewed as a cost‐effective approach that is universally prescribed as a first‐line treatment for nearly every chronic disease. Health care providers involved in the care for individuals with cerebral palsy (CP) are encouraged to take an active role in promoting their health and well‐being. Balancing activity behaviours across the whole day, with improved physical activity, reduced sedentary time, and healthy sleep behaviours, can set up infants, preschool‐, and school‐aged children with CP for a healthy trajectory across their lifetime. However, most clinicians do not apply a systematic surveillance, assessment, and management approach to detect problems with physical activity or sleep in children with CP. Consequently, many children with CP miss out on an important first line of treatment. This article presents an evidence‐informed clinical practice guide with practical pointers to help practitioners in detecting 24‐hour activity problems as a critical step towards adoption of healthy lifestyle behaviours for children with CP that provide long‐term health benefits.